2009
DOI: 10.1007/s11211-009-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Justifying Inequality: A Cross-Temporal Investigation of U.S. Income Disparities and Just-World Beliefs from 1973 to 2006

Abstract: This cross-temporal meta-analysis examined 6,120 American college students' scores on the Belief in a Just World Scale (BJW; Rubin and Peplau, J Soc Issues 31 (3): 1975) across the last three and a half decades. Drawing on models of belief threat, we examined whether the causal relationship between perceived injustice and increases in BJW could extend from the laboratory to society by using macro-economic injustice trends to predict changes in BJW across these decades. Specifically, we hypothesized that perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 57 publications
4
39
0
Order By: Relevance
“…Contrary to the expectations, we found that Kyrgyz students are higher in their JWB than the Turkish students in both general and personal Just world beliefs. These findings are in line with Umberson's (1993) study and the meta-analysis of Malahy et al, (2009), which found that while inequality increased so did just world beliefs. This supported the thesis that higher levels of just world beliefs, as is the case with the Kyrgyz sample, served as a stress buffering effect against the aftermaths of climbing poverty, joblessness, inequality, and corruption etc.…”
Section: Resultssupporting
confidence: 88%
“…Contrary to the expectations, we found that Kyrgyz students are higher in their JWB than the Turkish students in both general and personal Just world beliefs. These findings are in line with Umberson's (1993) study and the meta-analysis of Malahy et al, (2009), which found that while inequality increased so did just world beliefs. This supported the thesis that higher levels of just world beliefs, as is the case with the Kyrgyz sample, served as a stress buffering effect against the aftermaths of climbing poverty, joblessness, inequality, and corruption etc.…”
Section: Resultssupporting
confidence: 88%
“…To the extent that hierarchies are commonly the way in which systems are organized, defending the status quo often entails defending hierarchies (Gaucher, Kay, & Laurin, 2010;Kaiser et al, 2013). For example, system justification research demonstrates that even disadvantaged individuals who live in socially-stratified systems will bolster and defend a variety of hierarchies including stratification systems based on gender (Glick & S. T. Fiske, 2001;Jost & Kay, 2005;Laurin, Shepherd, & Kay, 2010), race (Jost, Pelham, & Carvallo, 2002), and economic circumstance (Kay, Czaplinski, & Jost, 2009;Kay & Jost, 2003;Malahy, Rubinlicht, & Kaiser, 2009). From a system justification perspective, therefore, support for hierarchies is often a means of fulfilling the broader motivation to believe that one's social systems are legitimate.…”
Section: Social Hierarchiesmentioning
confidence: 99%
“…Ferguson (2000) observed a reinforcement of the belief in a just world among members of the two groups before and after the cease-fire of 1994, which launched a growing wave of hope for peace in Northern Ireland. The importance of temporal and contextual variables was also emphasized in a recent cross-temporal meta-analysis by Malahy, Rubinlicht, and Kaiser (2009). This study revealed an increase in American college students' scores on a belief in a just world scale from 1973 to 2006.…”
Section: Stability Of Belief In a Just World?mentioning
confidence: 66%
“…At first sight, this conclusion may be at odds with the meta-analysis of Malahy et al (2009), who showed that increases in injustice due to income disparities were correlated with higher levels of belief in a just world. However, essential differences exist between the studies taken into consideration in this meta-analysis and the current study.…”
Section: Discussionmentioning
confidence: 96%